EFFECT OF HUMAN RESOURCE MANAGEMENT FUNCTIONS ON EMPLOYEES’ JOB STRESS IN OGUN OSUN RIVER BASIN DEVELOPMENT AUTHORITY ABEOKUTA, OGUN STATE, NIGERIA - ADEOGUN, S.O; ALABI, O.S; JOSHUA, Y; ABIONA, B.G.; HAROUN, O.A (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The workplace in the 21st century is synonymous with stress which if left unattended can slow down employees’ job performance. One of the activities of human resources management is to see to the overall well-being of the employees so that they can give their best to the organization. Therefore, the study examined the effect of HRM functions on the perception of job stress by employees of the Ogun Oshun River Basin Development Authority Abeokuta, Ogun State. A proportionate sampling method was used to select 133 respondents for the study out of which 122 of them completed the data collection process. Data was collected using a validated questionnaire. Relevant descriptive and inferential statistics were used to analyse the data collected. Results showed that the mean age of the respondent was 34years and 63.1% of the respondents were males. Many (67.2%) of the respondents hold HND/B.Sc. and a majority (88.5%) had less than 10 years of work experience. About 53.3% of the respondents earned less than ₦50,000 ($140) as monthly income. Results also showed that relationship within the organization is very good and thus ensures synergy (=3.22) and that members of staff possess the required skills to perform their job effectively, hence less supervision is required (x ̅=3.04). Chi-Square analysis showed no significant association between personal characteristics and perception of job stress while Correlation analysis showed a significant relationship between respondents’ perception of human resource management functions and perception of job stress (r=0.634, P<0.001) and between respondents’ responses to challenges of human resources management and perception on job stress (r=0.817, P<0.001). It was concluded that respondents’ perception of HRM functions and responses to challenges to HRM plays significant roles in their perception of job stress.